The metabolic change in serum lysoglycerophospholipids intervened by triterpenoid saponins from Kuding tea on hyperlipidemic mice. Issue 12 (29th November 2019) - Shi, Qingxin; Jin, Shuna; Xiang, Xingliang; Tian, Ji; Huang, Rongzeng; Li, Sen; Chen, Cheng; Xu, Hanlin; Song, Chengwu
Abstract : Triterpenoid saponins from Kuding tea have demonstrated preventive effects on hyperlipidaemia induced by a high-fat diet. Abstract : Triterpenoid saponins from Kuding tea have demonstrated preventive effects on hyperlipidaemia induced by a high-fat diet. Lysoglycerophospholipids (Lyso-GPLs) are known to be associated with proatherogenic conditions such as hyperlipidaemia. In this study, a target profiling strategy based on a multiple reaction monitoring mode was applied for the analysis of Lyso-GPLs. The metabolic changes were evaluated by the qualitative and relative quantitative distribution of six classes of Lyso-GPLs in mouse serum. A total of 153 Lyso-GPL regioisomers, consisting of 85 lysophosphatidylcholines, 15 lysophosphatidic acids, 23 lysophosphatidylethanolamines, 5 lysophosphatidylserines, 19 lysophosphatidylinositols and 6 lysophosphatidylglycerols, were detected and quantified. The results showed decreased trends in the content of total Lyso-GPLs in the serum of hyperlipidemic mice compared with that in normal controls. The content of total Lyso-GPLs significantly increased after treatment with triterpenoid saponins from Kuding tea. Among them, the proportions of most Lyso-GPLs with a higher degree of unsaturation or a longer carbon chain in fatty acyl chains dramatically decreased in hyperlipidemic mice. However, this tendency reversed after the treatment of triterpenoid saponins from Kuding tea. This is the first study regarding a target profiling strategy for the quantitative analysis of six different types of Lyso-GPLs on high-fat diet-induced hyperlipidemic mice intervened by Kuding tea. Those Lyso-GPLs changed significantly may be potential biomarkers for hyperlipidaemia, and involved in the mechanism of the preventive intervention of Kuding tea on Lipid metabolic diseases.